Response to an African-driven health agenda - Gitahi, Githinji (Lancet, 2017)
There is no question that Africa faces a myriad of health challenges and The Lancet Editorial (July 8, p 96)1 captured it well in the statement that “health is much more than just health care,” which reflects the absence of systems for health.